The Role of Promotion in Increasing the Competitiveness of Aquaculture Businesses Biofloc Tilapia F16_AQUACULTURE - Pahrul; Tahir, Sumiati; Asmayanti (Cita konsultindo, 2025)
This study aims to describe the role of promotion in increasing the competitiveness of biofloc tilapia fish farming business at F16_AQUACULTURE located in Makassar City. The approach used in this study is descriptive qualitative, with data collection methods through in-depth interviews and direct observation of business managers and employees. The results of the study indicate that the strategies implemented so far have focused more on product optimization and pricing, but there has been no planned and systematic promotion implementation. This has limited market reach and the absence of partnerships for large-scale product distribution. In today's digital era, promotion through social media and other digital platforms provides a huge opportunity to reach a wider consumer base. Promotional strategies such as collaboration with influencers, providing seasonal discounts, loyalty programs, and creating attractive promotional content are considered to be able to increase brand awareness and drive sales. Therefore, the implementation of a more adaptive and innovative promotional strategy is needed to strengthen the competitiveness and expand the F16_AQUACULTURE market amidst increasingly fierce competition.